Antifungal properties of rhamnolipid produced by Pseudomonas aeruginosa DS9 against Colletotrichum falcatum. (15th July 2015) - Goswami, Debahuti; Borah, Siddhartha Narayan; Lahkar, Jiumoni; Handique, Pratap Jyoti; Deka, Suresh
<x xml:space="preserve">Abstract</x> The rhamnolipid biosurfactant (RL‐DS9) extracted from the bacterial strain Pseudomonas aeruginosa DS9 was evaluated for its antifungal activity against Colletotrichum falcatum that causes red rot in sugarcane. The surface tension (ST) reduction, biosurfactant production, and antifungal activity of biosurfactant against C. falcatum were investigated by using the medium with different carbon sources and it was found to be maximum in glucose. Moreover, highest reduction of ST and production of biosurfactant was achieved at 4.5% (w/v) concentration of glucose. The efficacy of RL‐DS9 was compared with a commercially available rhamnolipid (RL‐R95) using microtitre plate assay. Results showed that at 100 μg ml−1 concentration RL‐DS9 exhibited 86.6% inhibition against C. falcatum spore germination, and in the same concentration RL‐R95 showed 83.3% inhibition. From liquid chromatography‐mass spectrometry (LC‐MS) analysis, it was revealed that only two similar congeners Rha‐(C10) and Rha‐Rha‐(C10:1) were found to be in common among both the rhamnolipids. In the plant bioassay test, it was noted that red rot incidence was reduced on the sugarcane plants treated with RL‐DS9. This is the first report that rhamnolipid biosurfactant produced by Pseudomonas aeruginosa DS9 could be able to control red rot disease of sugarcane caused due to the infection with the fungus Colletotrichum falcatum.